Penyuluhan kepada masyarakat tentang keefektifan obat hidroksikloroquin sebagai alternatif pencegahan dan pengobatan COVID-19 - Hendera Hendera; Dina ahsana; Muhammad Nadzir (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
COVID-19 infection is a disease with a very rapid spread and multiorgan failure can occur rapidly resulting in death in a short time. Many rumored treatments can ward off this infection, one of them is Hydroxychloroquine. The purpose of this community service activity is to provide correct information on the use of Hydroxychloroquine drugs in the prevention and treatment of COVID-19 and how to stop the spreading chain of infection to improve the degree of public health. This is a quantitative research with a Pre-Experimental method using One Group Pretest-Posttest Design and data collection instruments used are multiple choice question types. The results of 33 participant’s complete data were analyzed using statistics with the Wilcoxon test with a P-value of 0,000 (P <0.05). The results showed the participants got more clear the information about this Hydroxychloroquine  before and after education, this shows that the use of the method has succeeded in increasing the knowledge and understanding of participants about "The Effectiveness of Hydroxychloroquine Drug as Alternative Prevention and Treatment of COVID-19".